2011
DOI: 10.3892/etm.2011.418
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α -863 polymorphisms and the risk of hepatocellular carcinoma

Abstract: Abstract. Hepatocellular carcinoma (HCC) is a common type of highly malignant tumor. Guangxi is an area of China characterized by a high incidence of HCC. Previous epidemiological studies have found that chronic infection with hepatitis B virus (HBV) is one of the major etiological risk factors for HCC in China. With the increased understanding of the host immune response against HBV and the pathogenesis of the virus, at present, greater attention is being given to the immune response of cytokine genes, as pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 18 publications
0
12
0
1
Order By: Relevance
“…The TNF-a level is increased in the tumor microenvironment of HCC [27]. It regulates HCC carcinogenesis and progression by activating cell apoptosis [28,29]. In this study, we found that PRDX6, with iPLA2 activity, may act as a mediator for TNF-a-induced apoptosis in HCC.…”
Section: Discussionmentioning
confidence: 67%
“…The TNF-a level is increased in the tumor microenvironment of HCC [27]. It regulates HCC carcinogenesis and progression by activating cell apoptosis [28,29]. In this study, we found that PRDX6, with iPLA2 activity, may act as a mediator for TNF-a-induced apoptosis in HCC.…”
Section: Discussionmentioning
confidence: 67%
“…Polymorphism of TNF-α -863 C/A in the promoter region can in uence TNF-α expression, however, the result is still con icting. Some research suggest that it may increase TNF-α expression [49,50], while other research show the opposite result in which it may decrease TNF-α expression [27,51].…”
Section: Discussionmentioning
confidence: 99%
“…Each study has sample size ranged from 45 to 1,624 participants. Of all included studies in this metaanalysis, most studies came from Asia, in which 7 studies were from China [7,[22][23][24][25][26][27], 4 from Taiwan [15,[28][29][30], 2 from India [18,31], 2 from Korea [8,32], 1 was Japanese [33], 1 was Thai [34], and 1 was Turkey [35]. There were also some studies with non-Asian countries, including 2 from Egypt [36,37], 1 from Brazil [38], 1 from Italy [39], and 1 from Tunisia [40].…”
Section: Study Selectionmentioning
confidence: 99%
“…Similarly, Jung et al, studying 227 Korean patients with HCC and 365 controls, detected a higher frequency of allele -238*A among patients with HCC than among healthy controls [47]. On the other hand, Yang et al, did not find statistical difference in TNF-α -308G/ A alleles or genotypes frequencies between Chinese HCC patients (n=772) and healthy controls (n=852), but they observed that TNF-α -863AA genotype may increase the risk of HCC compared with the wild-type TNF-α CC [48].…”
Section: Il-18 (-607 C/a; Rs1946518 and -137 C/g; Rs187238) Ifn-γ (+mentioning
confidence: 93%